Detection of pneumonia using deep learning - Abd Eslem Sid (My University, 2025)
Pneumonia is among dangerous disease that affects the human lungs, and diagnosis at a later stage can lead to death. Diagnosis of infected patients in an early stage is necessary with a view to control the virus’ rapid spread. Chest radiography imaging represents an efficient tool for the diagnosis and follow-up Pneumonia. This dissertation aims to improve pneumonia detection from chest X-ray images using a hybrid model that combines Convolutional Neural Networks (CNN) and ResNet architectures. The combination is done at the flatten layer in order to diversify the features of models. After that the new flatten layer will be passed through the fully connected layers in order to learn more complex and abstract relationships between the merged features. We have tested our model on the dataset chest x-ray (pneumonia) and the obtained results show the effectiveness of our proposition compared with other methods cited in the state of the art. ---------------------------------------------------------------------------------- يُعدّ الالتهاب الرئوي من الأمراض الخطيرة التي تصيب رئتي الإنسان، وقد يؤدي تشخيصه في مرحلة متأخرة إلى الوفاة. لذا فإن الكشف المبكر عن المرضى المصابين يُعتبر أمرًا ضروريًا للحد من الانتشار السريع للفيروس. وتُعدّ صور الأشعة .السينية للصدر أداة فعّالة لتشخيص ومتابعة الالتهاب الرئوي يهدف هذا البحث إلى تحسين عملية الكشف عن الالتهاب الرئوي من خلال صور الأشعة السينية للصدر، وذلك باستخدام يتم دمج خصائص النموذجين عند ResNet. و (CNN) نموذج هجيني يجمع بين معماريتي الشبكات العصبية الالتفافية من أجل تنويع الخصائص المستخرجة، ثم تمر هذه الطبقة الجديدة عبر عدد من الطبقات layer) (flatten طبقة التسطّح .لتعلّم علاقات أكثر تجريدًا وتعقيدًا بين الخصائص المدمجة layers) connected (fully الكاملة الاتصال وقد تم اختبار النموذج المقترح على مجموعة بيانات خاصة بصور الأشعة السينية للصدر تتضمن حالات التهاب رئوي، وأظهرت النتائج فعالية الاقتراح مقارنة بالأساليب الأخرى المذكورة في الأعمال السابقة --------------------------------------------------------------------------------- La pneumonie est parmi les maladies dangereuses qui affectent les poumons humains, et un diagnostic à un stade ultérieur peut conduire à la mort. Le diagnostic des patients infectés à un stade précoce est nécessaire dans le but de contrôler la propagation rapide du virus. L’imagerie par radiographie thoracique représente un outil efficace pour le diagnostic et le suivi de la pneumonie. Ce mémoire vise à améliorer la détection de la pneumonie à partir d’images radiographiques thoraciques en utilisant un modèle hybride qui combine les architectures Con- volutional Neural Networks (CNN) et ResNet. La combinaison est effectuée au niveau de la couche flatten afin de diversifier les caractéristiques des modèles. Ensuite, la nouvelle couche flatten sera transmise à travers les couches entièrement connectées afin d’apprendre des relations plus complexes et abstraites entre les caractéristiques fusionnées. Nous avons testé notre mod- èle sur le jeu de données chest x-ray (pneumonia) et les résultats obtenus montrent l’efficacité de notre proposition par rapport aux autres méthodes citées dans l’état de l’art.
Keywords: Pneumonia detection; Chest X-ray; Deep learning; Artificial intelegence; Convolutional Neural Networks (CNN); ResNet; Image processing; CLAHE; Medical imaging; Hybrid model.; ﺍلكشف عن ﺍلالتهاﺏ ﺍلرئوي، ﺍلأشعة ﺍلسينية للصدﺭ، ﺍلتعلم ﺍلعميق، ﺍلذكاﺀ ﺍلاصطناعي، ﺍلشبكاﺕ ﺍلعصبية ﺍلالتفافية (CNN)، ResNet، معالجة ﺍلصوﺭ، CLAHE، ﺍلتصوير ﺍلطبي، نموﺫﺝ هجين.; Détection de la pneumonie; Radiographie thoracique; Apprentissage profond; Intelligence artifi- cielle; Réseaux de neurones convolutifs (CNN); Traitement d’image; Imagerie médicale; Modèle hybride.